Verification of 50- to 100-mer DNA and RNA sequences with high-resolution mass spectrometry. - Little, D P (1995)
Electrospray ionization with Fourier-transform mass spectrometry achieves accurate (< 50-ppm) determination of molecular weights of nucleotides, verifying structures of biological RNA and synthetic single-stranded DNA. High (1o(5)) resolving power makes possible detection of subpicomole impurities and adducts that confuse lower-resolution measurements. Molecular ions in a spectrum of 76-mer tRNA(Phe) had 34-55 Na adducts; when desalted, these show a molecular mass of 24,950.5 Da (expected, 24,950.3 Da) and minor variants at approximately -15 and +15 Da. A 50-mer DNA is characterized with < 10-ppm mass error, with detection of both N + 1 and N - 1 failure sequences. Special electrospray ionization conditions are necessary for a 72-mer to minimize fragmentation in the ion source. Despite the chemical noise from this, as well as failed sequences from automated synthesis, the spectrum of a 100-mer single-stranded DNA yielded a molecular mass of 30,702.4 +/- 1 Da, in good agreement with the expected value, 30,702.1 Da.